Prognostic value of the vasoactive-inotropic score in predicting outcomes following LVAD implantation - Taylor Pickering, DO; Kyle A. McCullough, MD; Cody W. Dorton, DO; David A. Rawitscher, MD; J. Michael DiMaio, MD; Nitin Kabra, MD; Greg Milligan, MD; Akash Rusia, MD; Patrick Ogbue, MD; Aasim Afzal, MD; Timothy J. George, MD (JHLT Open)
Background: Vasoplegia frequently complicates left ventricular assist device (LVAD) implantation, yet its impact on outcomes is not fully understood. The vasoactive-inotropic score (VIS), which quantifies vasoactive support, may predict outcomes in this population. Methods: A retrospective analysis of 146 patients undergoing HeartMate 3 LVAD implantation from 2017 to 2024 at a single institution was performed. VIS was calculated at 0, 6, 12, and 24 hours postoperatively, and the maximum VIS(VISmax) within the first 24 hours was determined: VIS = dopamine (mcg/kg/min) + dobutamine (mcg/kg/min) + 100*epinephrine (mcg/kg/min) + 10*milrinone (mcg/kg/min) + 10,000*vasopressin (units/kg/min) + 100*norepinephrine (mcg/kg/min). Patients were stratified by VISmax tertiles, and survival outcomes were compared using Kaplan-Meier estimates and Cox proportional hazards modeling. Secondary outcomes included predictors of vasodilation and postoperative complications. Results: The mean VISmax was 18.2 ± 10.1. Patients in the highest VISmax tertile (20-56) demonstrated lower 1-year survival (67.0% vs 84.3% vs 90.0%, p < 0.01). Preoperative Impella support (p = 0.02), elevated bilirubin (p < 0.01), and longer cardiopulmonary bypass time (p < 0.01) were predictors of increased VISmax. VISmax was an independent predictor of 1-year mortality (HR: 1.08[1.04-1.12], p < 0.01) and associated with increased odds of right ventricular assist device placement, renal replacement therapy, and tracheostomy (all p < 0.01). Hydroxocobalamin pre-treatment was associated with lower VISmax (15.65 ± 9.52 vs 19.40 ± 10.25, p = 0.04). Conclusion: Elevated VISmax is a predictor of morbidity and mortality following LVAD implantation. Strategies such as preoperative hydroxocobalamin administration may mitigate postoperative vasoplegia. Further studies are warranted to refine risk stratification and optimize management for these high-risk patients.